2008
DOI: 10.1179/crn.2008.037
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Laser Therapy in Temporomandibular Disorder: a Phase II Double-Blind Study

Abstract: The purpose of this study was to evaluate the analgesic effect of Low Intensity Laser Therapy (LILT) and its influence on masticatory efficiency in patients with temporomandibular dysfunction (TMD). This study was performed using a random, placebo-controlled, and double-blind research design. Fourteen patients were selected and divided into two groups (active and placebo). Infrared laser (780 nm, 70 mw, 60s, 105J/cm2) was applied precisely and continuously into five points of the temporomandibular joint (TMJ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 11 publications
0
53
0
1
Order By: Relevance
“…As a result of our search for research articles, 7 articles discussing clinical findings with a PEDro score of between 9 and 11 were selected to examine the pain relief effect of LLLT when treating TMJ pain15,16,17,18,19,20,21 ) . All of the treatment parameters and PEDro scores are shown in Table 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of our search for research articles, 7 articles discussing clinical findings with a PEDro score of between 9 and 11 were selected to examine the pain relief effect of LLLT when treating TMJ pain15,16,17,18,19,20,21 ) . All of the treatment parameters and PEDro scores are shown in Table 1…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the results are based on the treatment outcomes of 223 subjects in six articles15,16,17, 19,20,21 ) . Four of the articles showed a positive effect on pain relief after LLLT was employed15, 17, 19, 20 ) . But no statistically significant differences (p > 0.05) existed in the results of the studies of Emshoff et al16 ) and Venancio et al21 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Carrasco et al . [3] divided 14 patients into two groups (active and placebo) and concluded that low-intensity laser application is effective in reducing TMD symptoms, and also has influence over masticatory efficiency. Shirani et al .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is disturbing to see the number of patients with TMD treated with non-evidence-based therapies 6 , often without competent professional assistance 37 . As an alternative therapy, LLLT with its analgesic, anti-inflammatory, anti-edematous, and biostimulatory effects has proven to be effective in reducing pain and muscle tension in patients with TMD 7,9,16,21,23,26,35,38 . …”
Section: Discussionmentioning
confidence: 99%
“…26 (2007); and Carrasco, et al. 7 (2008), who used panoramic radiography, should be analyzed with caution because there is not always a direct association between the findings of such examinations and the presence of signs and symptoms of TMD 1,33 . …”
Section: Discussionmentioning
confidence: 99%